(untitled) (Fiep Bulletin - online, 2015)
Overweight and sedentarism indexes in children and adolescents have been constantly increasing in the past few decades. Considering these aspects, the objective of this study is to verify the overweight and obesity prevalence and the physical activity levels in students attending grade school or high school in Public Educational Institutes in Lapa-PR municipal rural district. The subjects being studied were 193 students, 101 males and 92 females, attending grade school or high school in Public Educational Institutes in Lapa-PR municipal rural district. The Body Mass Index (BMI), based on the classification proposed by CDC, was used to verify the overweight and obesity prevalence. The level of physical activity was measured through IPAQ. At first the qui-square analysis was used to verify the probable associations between the levels of physical activity and the adolescents’ body mass index by sex and total sample. However, no significant association was observed. Thus, the descriptive analysis through the percentile frequencies of the indicators was used to verify the behavior of the sample in relation to overweight and obesity prevalence and physical activity levels. The results showed a total overweight of 8.9% in males and 8.7% in females, respectively. Coincidentally the indexes for obesity and low weight were identical for both sexes (only 1.0% in males and 2.2% in females, respectively). Most of the adolescents were classified as active and/or very active, being 33.6% of active boys and 54.3% of active girls, and 63.4% in very active boys and 43.5% in very active girls. It can be concluded that overweight and obesity prevalence was low among the students attending grade school or high school in Public Educational Institutes in Lapa-PR municipal rural district, possibly because the great majority of the adolescents presented active or very active levels of physical activity.